SUBACUTE OTITIS EXTERNA IN CATS CAUSED BY OTODECTES CYNOTIS INFESTATION WITH BACTERIAL INFECTIONS - Arinata, I Ketut Teguh; Arjentinia, I Putu Gede Yudhi; Suartha, I Nyoman (Buletin Veteriner Udayana, 2025)
Otitis is the most common cases that found in companion animal practitioners. Otitis defined as an inflammation that occurs in the ear canal that can be classified based on the location of the inflammation. Otitis externa is a term used for otitis that occurs in the ear canal, specifically outside the tympanic membrane. This disease can be caused by fungal, parasitic and bacterial infections. The main aim of this article is described the treatment of otitis externa in cats with mixed-infection by parasitic and bacterial infection. An intact female domestic cat ages seven months old, has had frequently shaking its head and scratching its ears for the past 3 weeks. On physical examination, dark cerumen was found on the right ear, and purulent lesions founded on the left ear and left forelimb paw. Laboratory examinations using swabbed on the ear canals that shows parasitic infections. Furthermore, from cytology was found inflammation cells and coccus-shaped bacteria on left ear, while rod-shaped bacteria on left forelimb paw. The isolation and identification of bacteria indicated the presence of secondary infections by Staphylococcus spp found on the ears. The cat was diagnosed with otitis externa with a good prognosis. The therapy carried out was by administration antibiotic namely Co-amoxiclav (Claneksi®) in the form syrup for 10 days, antiparasitic ear drops namely Ivermectin 0,02% (Vet-Otic®) for 7 days and anti-inflammatory drugs with methylprednisolone acetate tablet orally for 3 days. Evaluation of therapy conducted after 10 days of drugs administration that show an improvement of the cat’s health as indicated by the absence of head shaking and unseen of excessive cerumen, as well as a gradual decrease in the level of pruritus, and owners are advised to keep the cat's ears and environment clean, not allowing the cat to roam free